2021
DOI: 10.1111/1749-4877.12542
|View full text |Cite
|
Sign up to set email alerts
|

The biogeography of group sizes in humpback dolphins (Sousa spp.)

Abstract: Humpback dolphins (Sousa spp.) are obligate shallow-water and resident species, and they typically live in fissionfusion societies composed of small-sized groups with changeable membership. However, we have scant knowledge of their behavioral ecology, starting with potential factors influencing inter-population variability of their group sizes. Here, we compiled a new global dataset of humpback dolphin group sizes based on 150 published records. Our data indicated an inter-specific consistency of group-living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…This study made the first attempt to sample comparable group size of humpback dolphins from different geographic regions by using two methods simultaneously. Our data clearly revealed that dolphin group size across three sampling regions, no matter from observer-based counts or photo-identification, were highly variable, typically including single individual, small pairs, and rarely middle-to-large aggregations of several tens (Parsons, 2004;Würsig et al, 2016;Liu et al, 2021c). Notably, small groups with ≤10 members were the most frequently encountered (80-90%), while only a small proportion (<5%) were large groups with >30 members.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…This study made the first attempt to sample comparable group size of humpback dolphins from different geographic regions by using two methods simultaneously. Our data clearly revealed that dolphin group size across three sampling regions, no matter from observer-based counts or photo-identification, were highly variable, typically including single individual, small pairs, and rarely middle-to-large aggregations of several tens (Parsons, 2004;Würsig et al, 2016;Liu et al, 2021c). Notably, small groups with ≤10 members were the most frequently encountered (80-90%), while only a small proportion (<5%) were large groups with >30 members.…”
Section: Discussionmentioning
confidence: 69%
“…A group was considered as AAC when G observer was ≤10 individuals, indicating that all or almost all individuals were captured in the group (Tyne et al, 2014;Hupman et al, 2018). A threshold, i.e., 10 was selected because humpback dolphins were often observed in small groups with ≤10 individuals (Parsons, 2004;Würsig et al, 2016;Liu et al, 2021c). For AC groups, we calculated the photo-identification group size G photo by counting the number of D1, D2, and D3 individuals present.…”
Section: Photo-identificationmentioning
confidence: 99%
See 3 more Smart Citations